2021
DOI: 10.2478/jolace-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of beginning and advanced teachers in managing various changes in their profession

Abstract: The paper is devoted to obtaining information on the resilience of kindergarten and primary school teachers. In the research, special attention was paid to beginning teachers, who we thought were more likely to be less resilient than teachers with longer experience. The research sample consisted of teachers of selected kindergartens and primary schools throughout the Czech Republic. The aim of the research was to find out whether there are differences in resilience between selected groups of teachers due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Regarding the sociodemographic variables of teachers that have been analyzed to examine their relationship with resilience, some studies did not observe significant differences as a function of gender, age, years of experience and educational level at which teaching is provided [ 13 , 25 , 48 ]. On the contrary, there are studies that found a higher level of resilience in women than in men [ 47 ], higher level of resilience in teachers with a greater number of years of teaching experience versus novice teachers [ 46 , 49 ] and higher level of resilience in teachers who had higher or additional studies (master’s vs. bachelor’s degrees or with doctoral studies) [ 25 , 50 ]. Thus, the need for further exploration into variables that may influence the development of teacher resilience arises.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the sociodemographic variables of teachers that have been analyzed to examine their relationship with resilience, some studies did not observe significant differences as a function of gender, age, years of experience and educational level at which teaching is provided [ 13 , 25 , 48 ]. On the contrary, there are studies that found a higher level of resilience in women than in men [ 47 ], higher level of resilience in teachers with a greater number of years of teaching experience versus novice teachers [ 46 , 49 ] and higher level of resilience in teachers who had higher or additional studies (master’s vs. bachelor’s degrees or with doctoral studies) [ 25 , 50 ]. Thus, the need for further exploration into variables that may influence the development of teacher resilience arises.…”
Section: Introductionmentioning
confidence: 99%